TINJAUAN HUKUM PIDANA ISLAM TERHADAP KEJAHATAN DI BIDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Meuthia Sari Siregar; Abdul Hadi; Jumanah Jumanah (Universitas Islam Negeri Raden Fatah Palembang, 2021)
ABSTRACT This thesis is entitled Review of Islamic Criminal Law Against Crimes in the Field of Information and Electronic Transactions (Study of Bitcoin Investment Fraud Through the Memiles Application, this thesis answers two questions; First, Criminal Sanctions Against Crimes in the field of information and electronic transactions (Study of Bitcoin Investment Fraud). In the Memiles Application, Second, Sanctions in terms of Islamic Criminal Law Against Crimes in the field of information and electronic transactions (Study of Bitcoin Investment Fraud in the Memiles Application. The research used in this study is through aapproach library research ). used is secondary data consisting of three parts, namely, primary legal materials, secondary legal materials and tertiary legal materials.Primary legal materials are binding legal materials in the form of the Qur'an and Hadith, the 1945 Constitution, and regulations applicable. Results discussion in terms of Huk um is takzir sanctions where the sanctions are determined based on local ulil amri (law enforcement authorities), then the criminal sanctions from ta'zir are the applicable laws, namely Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. Keywords: Fraud, Information and Electronic Transactions, Investment, Memiles Application, Ta'zir.